Impact of a Clinical Decision Support System (CDSS) on the Stewardship of Meropenem and Tigecycline in a Tertiary Hospital - pudpong, korawan; Chaphakdee, Praphatsorn; Gatechan, Tipanong; dowwongyat, Nidtaya (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Antimicrobial resistance (AMR) is a global health crisis that compromises clinical outcomes and increases healthcare costs, particularly concerning broad-spectrum antibiotics like Meropenem and Tigecycline. This study aimed to evaluate the impact of a computer-assisted Clinical Decision Support System (CDSS) on prescribing appropriateness, antibiotic consumption, and the efficiency of Antimicrobial Stewardship (AMS) programs. Methods A pre-post intervention study was conducted at a 1,188-bed tertiary care hospital, comparing a 12-month pre-intervention period (Jan–Dec 2022) with a 6-month post-intervention period (Jan–Jun 2023). The intervention involved an integrated CDSS within the Hospital Information System. Key outcomes included prescribing appropriateness, antibiotic consumption trends (DDD/100 patient-days) analyzed via Interrupted Time Series (ITS), and physician acceptance rates. clinical outcomes included clinical improvement during treatment, defined as documented improvement in clinical status, such as normalization of body temperature, hemodynamic stability, or no need for escalation or modification of antimicrobial therapy due to clinical deterioration. Results Following CDSS implementation, the overall appropriateness of antibiotic prescribing increased significantly from 56.33 % to 94.08 %, with 100% data completeness in drug requisitions. Tigecycline consumption showed a significant downward trend (p=0.0067), with a reduction of -512.545 DDD/100 patient-days per month. Redundant AMS interventions dropped from 43.67% to 5.92%, while the physician acceptance rate for CDSS and pharmacist recommendations reached 100%. Clinical improvement was observed in 54.10% of patients in the post-intervention group. Conclusions and Recommendations The integrated CDSS effectively optimized the use of restricted antibiotics, reduced overall drug consumption, and streamlined AMS workflows. These findings suggest that digital CDSS interventions are scalable models for improving rational drug use. Future initiatives should expand the application to other restricted antimicrobials and further develop medication systems to ensure real-time rational drug use across various levels of healthcare facilities.